Key Factors of BIM Implementation for Interior Design Firms in Malaysia - Abd Hamid, Abu Bakar; Embi, Mohamed Rashid (International Journal of Sustainable Construction Engineering and Technology, 2020)
Building Information Modelling (BIM) is a process to improve and innovative tools for visualize the design phases, to coordinate the projects and to communicate the drawings and documentations as well as innovative technology in the construction industry. In Malaysia, BIM previously implemented by Architecture, Engineering and Construction (AEC) but in the Interior Design (ID) industry is a new approach and the lacking of knowledge is the issue for interior design industry to implement BIM. This research is to identify the key factors of BIM implementation in the interior design industry from the analysis of research and literature review. Mix-method was applied in this research and data were analysed to identify the key factors in this research. Research was found several of key factors in the interior design industry while using BIM in Malaysia. These factors will be isolated as variables and barriers for BIM implementation.